2021
DOI: 10.1002/ecs2.3725
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and novel application ofN‐mixture models for aerial surveys of wildlife

Abstract: Aerial surveys are a critical tool for inference of wildlife populations, yet are limited by current available methods to account for imperfect detection without marking animals. N-mixture models use count data from replicate surveys for estimation of wildlife abundance while accounting for imperfect detection. This statistical framework was recently developed but is rarely applied to aerial surveys of terrestrial wildlife. We applied an N-mixture model incorporating temporary emigration to a novel aerial surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…However, despite these raised concerns, studies comparing N‐mixture models with more traditional and well‐established approaches (i.e. capture‐recapture models or distance sampling) have generally shown similar results (Christensen et al, 2021; Ficetola et al, 2018; Keever et al, 2017; Kéry, 2018). In the context of drone‐based surveys, the impact of these findings would be expected to be more concerning for the availability process (non‐modelled heterogeneity in unavailability).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite these raised concerns, studies comparing N‐mixture models with more traditional and well‐established approaches (i.e. capture‐recapture models or distance sampling) have generally shown similar results (Christensen et al, 2021; Ficetola et al, 2018; Keever et al, 2017; Kéry, 2018). In the context of drone‐based surveys, the impact of these findings would be expected to be more concerning for the availability process (non‐modelled heterogeneity in unavailability).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the effects of spatial temporary emigration, one could plan sampling design to (i) shorten the time interval between repeated visits (but avoiding temporal autocorrelation) and (ii) define site size as relatively large in comparison with the expected area used by the individuals during sampling. Christensen et al (2021) proposed a post hoc sensitivity analysis to define the best length to split flight lines into sites and found that the ideal size is similar to the home range size reported to the target species. Auxiliary data from telemetry or some marked individuals can provide information to segregate the two components of temporary emigration (spatial and temporal; Brack et al, 2018).…”
Section: N‐mixture Models For Spatiotemporally Replicated Drone Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Without access to known truth, we could not investigate whether the estimates produced reflect true relationships between covariates and species abundance, so we cannot say whether either N-mixture models or GLMMs estimated parameters accurately in that sense. We suggest that practitioners interested in modeling relative abundance from count data consider the assumptions of both models, including known features of N-mixture model robustness in practice and theory 10 , 11 , 13 , 14 , 16 – 18 , 20 23 , along with other practical trade-offs. If both GLMMs and N-mixture models are potentially appropriate, we recommend the model selection and goodness-of-fit checking procedure outlined in this paper for choosing the most parsimonious model with adequate fit.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kéry 19 identified estimation instability, likely attributable to a likelihood maximum in the limit of zero detection 18 , but recommended the use of N-mixture models when estimation instability does not occur 19 . Several studies have found that the N-mixture model produces estimates of absolute abundance that agree with more rigorous sampling methods 20 23 though this finding is not universal 24 . Still, established sensitivities and computational pathologies are grounds for caution in recommending N-mixture models when data do not strictly conform to modeling assumptions.…”
Section: Introductionmentioning
confidence: 99%